A theoretical study on the decomposition of TKX-50 with different vacancy defect concentrations under shock wave loading - Jun-qing Yang; Zhi-wei Guo; Xiao-he Wang; Ga-zi Hao; Yu-bing Hu; Xiao-jun Feng; Rui Guo; Wei Jiang (Energetic Materials Frontiers)
This study investigated the impacts of different vacancy defect concentrations on the decomposition of dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50) under shock wave loading using the ab initio molecular dynamics (AIMD) method combined with the multiscale shock technique (MSST). Initially, eight crystal models of TKX-50 with vacancy defect concentrations of 0 %, 3.13 %, 6.25 %, and 9.38 % were established. The most stable models at these defect concentrations were identified as V0, V1.1, V2.1, and V3.1, respectively by calculating the vacancy formation energies. Afterward, the decomposition processes of these most stable models under shock waves at a speed of 10 km s−1 were examined in detail. The results show that TKX-50 underwent reversible proton transfer processes under shock wave loading, which are similar to its behavior under thermal loading. With an increase in the vacancy defect concentration, the TKX-50 systems became significantly more unstable and compressible, a greater variety and quantity of small gas molecules were quickly generated, and more pronounced fluctuations in the cluster quantities and molecular weight of the largest clusters were observed. These findings demonstrate that vacancy defects can accelerate the decomposition of TKX-50, providing theoretical insights into the damage evolution of TKX-50 under shock wave loading.